INTERNAL DOSE DETERMINATION ON HUMAN AS RESULT OF PROCESSED KANGKUNG (IPOMOEA REPTANS) CONSUMPTION CONTAMINATED BY RADIONUCLIDE CESIUM-134 AND STRONTIUM-85 - Putra, Didi Prabowo; S. Salami, Indah Rachmatiah; Tjahaja, Poppy Intan (ITB Journal Publisher, LPPM ITB, 2009)
Abstract: Research has been done to find out internaL dose that can be received by human as result of consumption kangkung that growth in contaminated soil by caesium-134 and strotium-85. Kangkung was planted in soil contaminated with caesium-134 and strontium-85 for 70 days. After harvesting, a part of the plant separated and the other part being washed and boiled and then the radionuclide content for all of the plant were measured using spectrometer gamma. From the measurement and calculation, washing, boiling and sauteing process gives quite significant impact in reducing activity percentage of radionuclide which were about 23,5, 14,4 and 9,8 for strontium- 85 and 28,2, 58,5 and 47,4 for caesium-134. The result of equivalent dose calculation showed that each internal dosesis still bellow the limit of 5 mSv/year, and the dose was 0,053 mSv/year until 0,137 mSv/year. Key words: kangkung, contamination, cesium-134, strontium-85, activity, internal dose Abstrak: Penelitian dilakukan untuk mengetahui dosis interna yang dapat diterima oleh manusia akibat mengkonsumsi kangkung yang tumbuh pada tanah terkontaminasi oleh radionuklida cesium-134 dan stronsium-85.Penelitian dilakukan dengan cara menanam tanaman kangkung pada media tanah terkontaminasi Cs-134 dan Sr-85selama 70 hari. Setelah panen, sampel tanaman diproses dengan pencucian, perebusan dan penumisan kemudiadiukur kandungan radionuklidanya dengan menggunakan spektrometer gamma. Dari hasil pengukuran diperolehbahwa ketiga proses memberikan pengaruh yang cukup besar terhadap penyisihan radioaktivitas dari sampeltanaman, yaitu sebesar 23,5, 14,4 dan 9,8 untuk stronsium-85 dan 28,2, 58,5 dan 47,4 untuk cesium-134. Hasilperhitungan dosis ekivalen menunjukkan nilai dosis interna dari masing-masing radionuklida berada dibawahambang batas sebesar 5 mSv/tahun, yaitu bernilai antara 0,053 mSv/tahun sampai 0,137 mSv/tahun.